The typical sand-fixing plants in the Ulan Buh desert-oasis area significantly changed the distribution pattern of surface sediments - An, Hua; Zhao, Feiyan; Li, Haonian; Meng, Zhongju; Ding, Hailong; Ding, Yanlong; Qin, Lei; Xin, Jing (Frontiers in Environmental Science, 2025)
Vegetation increases surface roughness, reduces wind speeds and decreases sand carrying capacity, thereby effectively intercepting wind-sand flows and promoting sand deposition. Exploring the distribution of sand-fixing plant sediment particles and the characteristics of plant morphology parameters in the desert-oasis transition zone can provide a certain theoretical foundation for regional ecological vegetation construction and desertification control. In this paper, the particle size of surface sediments (0–2 cm) under cover of five typical sandy vegetation in the desert-oasis transition zone at the northeastern edge of the Ulan Buh Desert was investigated, and the effects of plant morphometric parameters on the grain size distribution of sediments were analyzed. The results show: (1) Plant spatial configuration significantly influenced surface sediment characteristics, with Nitraria tangutorum having the largest crown width and number of branches with 283 cm and 385 branches compared to the other four species. In unit area, the degree of porosity from large to small is: Psammochloa villosa > Agriophyllum squarrosum > Phragmites australis > Artemisia ordosica > Nitraria tangutorum. On the whole, the interception effect of N.tangutorum shrub on transit airflow is more prominent. (2) The grain size distribution of the sandy material in the study area is unimodal with good particle sorting. Due to the interception of N. tangutorum and A. ordosica shrubs, the contents of medium sand and fine sand in the mechanical composition of sediments in the surface layer of vegetation-covered dunes decreased significantly, while the contents of clay, silt, and very fine sand increased significantly (P < 0.05); Compared to the bare dunes, the particle sorting becomes worse, and the particle size frequency curve shifts to a bimodal state with a positively skewed trend and a lower kurtosis value. Overall, the sediment grain composition in order of coarseness to fineness was: CK > P. villosa > A. squarrosum > P. australis > A. ordosica > N. tangutorum. (3) The mean grain size of sediments under vegetation coverage was positively correlated with sortability, kurtosis and skewness (P < 0.01). Mean particle size and sortability significantly correlated negatively with kurtosis and skewness (P < 0.01). (4) Mean grain size and sortability were significantly positively correlated with plant crown width and branch number and significantly negatively correlated with porosity (P < 0.05). Skewness and kurtosis were significantly negatively correlated with plant crown width and branch number and significantly positively correlated with porosity (P < 0.05). (5)In this paper, the mean grain size of the sediment is used as an indicator of the above-mentioned plant windbreak and sand fixation. It is concluded that the lower leaves of N. tangutorum and A. ordosica are dense, the porosity is minor, and the particle composition of the sand material is fine, forming dense vegetation shrubs on the dunes, which is more powerful in windbreak and sand fixation. Screening plants with strong vitality and outstanding sand-fixing capacity is important for controlling quicksand, improving soil quality and preventing wind erosion.